2012
DOI: 10.2478/s11535-012-0084-6
|View full text |Cite
|
Sign up to set email alerts
|

The effect of mental rotation on changes in plasma testosterone and cortisol levels

Abstract: Testosterone level has an influence on cognitive functions, especially spatial abilities. The relationship is, however, bidirectional and brain activity also affects testosterone levels. The aim of this study was to analyze the effects of an intensive 3D mental rotation task on testosterone levels in young healthy men and women. In the mental rotation task, men reached a higher top score (P=0.027) and total score (P=0.004) compared to women. In 8 out of 9 women (P=0.008) but not in men (P=0.129) testosterone l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2015
2015
2015
2015

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 23 publications
1
1
0
Order By: Relevance
“…That finding may not be surprising, because differences between the sexes in visuospatial processing, as assessed by tests of mental rotation (ie, the participant manipulating the image of an object in their mind), consistently demonstrate a large effect size (Cohen d = 0.57) . Visuospatial ability is also a cognitive domain in which testosterone titers in men have been linked directly to performance superiority . It is noteworthy that the findings from the recent meta‐analysis are consistent with the review by Jamadar et al and the results from an fMRI study by Cherrier et al In general, however, it is premature to conclude that visuospatial processing is the only area in which ADT impairs cognitive function.…”
Section: Introductionsupporting
confidence: 74%
“…That finding may not be surprising, because differences between the sexes in visuospatial processing, as assessed by tests of mental rotation (ie, the participant manipulating the image of an object in their mind), consistently demonstrate a large effect size (Cohen d = 0.57) . Visuospatial ability is also a cognitive domain in which testosterone titers in men have been linked directly to performance superiority . It is noteworthy that the findings from the recent meta‐analysis are consistent with the review by Jamadar et al and the results from an fMRI study by Cherrier et al In general, however, it is premature to conclude that visuospatial processing is the only area in which ADT impairs cognitive function.…”
Section: Introductionsupporting
confidence: 74%
“…However, the interaction between testosterone and mental rotation tests is bidirectional. It has been shown that mental rotation testing affects testosterone, at least in women (Durdiakova et al, 2012 ). In Table 3 , published experimental data on the effects of testosterone on spatial abilities are summarized.…”
Section: Spatial Abilitiesmentioning
confidence: 99%